2018
DOI: 10.29322/ijsrp.8.10.2018.p8233
|View full text |Cite
|
Sign up to set email alerts
|

Starch and Karyotype Study of Taro (Colocasia esculenta L.) from West Sumatra, Indonesia

Abstract: The shape, amount, and distribution of starch granules are specific to each plant. Different plants will have different shapes, quantities, and distribution of starch granules. Based on the shape, amount and distribution of starch, the types of starch producing plants can be classified. Taro (Colocasia esculenta L .) is a starch-producing plant that has the potential to be developed in the future. Colocasia esculenta L is distributed in a wide area in West Sumatra, Indonesia so that genetic variations and vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…This study found karyotype asymmetry with satellite-chromosomes, while Senavongse et al (2018) reported karyotype symmetry with satellite-chromosomes of C. esculenta (L.) Schott because of the effects of environmental factors. These cytological data can be used as evidence in the study of evolutionary relationships and can also help to identify the species (Senavongse et al 2020) as an important taxonomic character (Wahidi and Nursyahra 2018). Idiograms of both taros are reported for the first time.…”
Section: Resultsmentioning
confidence: 97%
“…This study found karyotype asymmetry with satellite-chromosomes, while Senavongse et al (2018) reported karyotype symmetry with satellite-chromosomes of C. esculenta (L.) Schott because of the effects of environmental factors. These cytological data can be used as evidence in the study of evolutionary relationships and can also help to identify the species (Senavongse et al 2020) as an important taxonomic character (Wahidi and Nursyahra 2018). Idiograms of both taros are reported for the first time.…”
Section: Resultsmentioning
confidence: 97%